The papar land protest, 1910-11 - Wong, D.T.K. (Cambridge University Press, 2012)
One of the recurring problems that emerged during the height of European expansion into Southeast Asia was the encroachment of European enterprises into indigenous lands. In most cases, problems existed especially in the manner that landholdings were understood by the natives vis-à-vis the new land laws introduced by the colonial powers. This often led to disputes which resulted in the natives being deprived of their rights. This paper looks into a case where the Dusun in Papar, North Borneo — an indigenous people — took the European colonial government to court over land rights which involved land encroachments by European enterprises and railways. The event took place barely 30 years after the first contact with European civilisation took place. The paper will examine the nature of the case and also investigate the role played by the Dusun and their fight against the government. The paper will also investigate the role of an English lawyer retained by the Dusun for the case, and that of the Roman Catholic Mission in championing the affairs of the indigenous people.